2013
DOI: 10.1111/jac.12029
|View full text |Cite
|
Sign up to set email alerts
|

Systemic View on Heading and Overwintering: Are They Always Opposed?

Abstract: The study investigated the cultivars of non-obligatorily requiring vernalization plant Festulolium braunii and assessed the influence of non-hardy reproductive and hardy vegetative structures on overwintering effect. The study was conducted taking into account systemic relations between these types of structures. The results show the cultivars differ according to the percentage of headed and overwintered plants, when the cultivars with the most abundant heading -'Felopa' and 'Sulino' -are also better at overwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Indeed, a re-examination of the marker data of Alm et al (2003) showed that, in the F 1 population, the maternal marker haplotype of the VRN1 -region associated with the ability to head without vernalization was also the one that was associated with better freezing tolerance after 2 weeks of CA (the paternal haplotypes did not have different effects on these traits in F 1 ). Šimkūnas et al (2013) also found a positive correlation among Festulolium cultivars between heading prior to vernalization and survival in the field during the following winter. They speculated that this might be due to more young tillers in the plants heading prior to vernalization, but had no data supporting this.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, a re-examination of the marker data of Alm et al (2003) showed that, in the F 1 population, the maternal marker haplotype of the VRN1 -region associated with the ability to head without vernalization was also the one that was associated with better freezing tolerance after 2 weeks of CA (the paternal haplotypes did not have different effects on these traits in F 1 ). Šimkūnas et al (2013) also found a positive correlation among Festulolium cultivars between heading prior to vernalization and survival in the field during the following winter. They speculated that this might be due to more young tillers in the plants heading prior to vernalization, but had no data supporting this.…”
Section: Discussionmentioning
confidence: 66%